Korelasi Antara Kualitas Layanan Loket dan Kepuasan Wajib Pajak pada Kantor Samsat Aceh Tamiang - Sari, Maya Puspita; Yunus , Said; Karnelis; Refi, T. Muana (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2023)
This research aims to analyze the correlation between the quality of counter service and taxpayer satisfaction at the Aceh Tamiang District Samsat Office. The services provided by counter officers at Samsat have the potential to influence taxpayers' perceptions and levels of satisfaction. The research method is to collect primary data which has previously been supported by secondary data by: Interview. A data collection activity by conducting interviews at the Aceh Tamiang District Samsat Office. Observation (Observation) Data collection activities by direct observation of research objects at the Aceh Tamiang Regency Samsat Office. Questionnaire (Questionnaire) Data collection activities. The research results show that there is a significant positive correlation between the quality of counter service and taxpayer satisfaction. These findings indicate that improving the quality of counter services at the Samsat Office can increase taxpayer satisfaction, which in turn can encourage increased taxpayer awareness and compliance in fulfilling tax obligations.